The People's Right to the Novel : War Fiction in the Postcolony - Coundouriotis, Eleni (Book collections on Project MUSE., 2014)
"This study offers a literary history of the war novel in Africa and argues for the genre's distinct contribution to the literary culture of the continent. The war novel is a form of people's history that participates in a political struggle for the rights of the dispossessed"--